Quality Education for All. A Subjet of Human Rights. Proposal for the Discussion on Educative Policies - Martha Vargas de Avella (Universidad Autónoma de Madrid, 2018)
Commentaries to the Document: The Right to a Quality Education for All in Latin American and the Caribbean